Computer science : an overview - Brookshear, J. Glenn (Redwood City, California : Benjamin Cummings, 1994)
This unique book offers a readable survey of computer science, covering a wealth of topics and equipping the reader with an understanding of the scope of the science as well as the terminology in the field. This new edition contains new sections reflecting the growing importance of object-oriented methodologies in programming and database design.
Introduction -- Part One Machine Architecture -- Part Two Software -- Part Three Data Organization -- Part Four -- The Potential of Algorithmic Machines -- Appendix A Popular Codes -- Appendix B A Typical Machine Language -- Appendix C Insertion Sort in Assembly Language -- Appendix D Syntax Diagrams for Pascal -- Appendix E The Equivalence of Loop and Recursive Structures -- Appendix F Answers to Questions/Exercises -- Index.
Includes bibliographical references and index.
Keywords: COMPUTER SCIENCE